2011
DOI: 10.1021/jf202975x
|View full text |Cite
|
Sign up to set email alerts
|

Residue Analysis and Degradation Studies of Fenbuconazole and Myclobutanil in Strawberry by Chiral High-Performance Liquid Chromatography–Tandem Mass Spectrometry

Abstract: A simple and sensitive enantioselective method for the determination of fenbuconazole and myclobutanil in strawberry was developed by high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). Fenbuconazole and myclobutanil residues in strawberry were extracted with acetonitrile containing 1% acetic acid, and an aliquot was cleaned up with PSA (primary and secondary amine) and C(18) sorbent. The direct resolution of fenbuconazole and myclobutanil enantiomers was performed on a cellulose tris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 27 publications
(33 reference statements)
2
34
0
1
Order By: Relevance
“…The fit was good with r 2 > 0.8688 in most cases. The half‐life of pesticides in plants is an important indicator of pesticide efficacy and pollution . Our data showed that the half‐lives of (+)‐hexaconazole and (−)‐hexaconazole were 3.37 and 4.28 days in tomato and 5.98 and 6.92 days in cucumber, respectively.…”
Section: Resultsmentioning
confidence: 78%
“…The fit was good with r 2 > 0.8688 in most cases. The half‐life of pesticides in plants is an important indicator of pesticide efficacy and pollution . Our data showed that the half‐lives of (+)‐hexaconazole and (−)‐hexaconazole were 3.37 and 4.28 days in tomato and 5.98 and 6.92 days in cucumber, respectively.…”
Section: Resultsmentioning
confidence: 78%
“…The results demonstrated that the degradation of myclobutanil enantiomers in rat liver microsomes was in accordance with the first-order kinetics equation, and the regression equation of (+)-myclobutanil was y = 35.7468 e -0.0816x , R 2 = 0.9905 and the regression equation of (-)-myclobutanil was y = 31.8824 e -0.0072x , R 2 = 0.9602. 17 The study indicated the enzymatic stereoselective behavior of myclobutanil enantiomers in organisms and other environmental matrices. Significant enantioselectivity was observed in degradation rates between the two enantiomers of myclobutanil in rat liver microsomes.…”
Section: Kinetic Degradation In Rat Liver Microsomesmentioning
confidence: 94%
“…Yoshii reported that glutathione reductase (GR) originating in wheat could degrade malathion and phenthoate, it is likely that GR acted on the specific structure of malathion and phenthoate, the S P S bond, and the blanch structure bonding with the sulfur atom [43]. Thus, it is possible that activation of plant enzymes may cause enantioselective degradation of residual pesticides [44].…”
Section: Degradation Of Malathion In Vegetables and Cropsmentioning
confidence: 99%